Bonus Demografi: Peluang atau Tantangan Bagi Kemajuan Indonesia di Tahun 2045 - Nuriman, Eki Jaki; Hidayat, Rahmat; Setiabudi, Adi; Dewi, Maya Puspita (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Indonesia's demographic bonus, characterized by an increase in the number of people of productive age, provides an excellent opportunity to drive economic growth and sustainable development. However, optimizing the demographic bonus faces various challenges, including disparities in the quality of education, inequality in access to skills training, and the unpreparedness of the labor market to absorb the workforce. This study aims to analyze the potential of the demographic bonus as an economic opportunity while identifying challenges that hinder its optimization. With an innovative cross-sectoral approach involving education, health, and the economy, this research offers solutions in the form of strengthening the quality of human resources through technology-based education, digital skills training, and cross-sectoral policy synergies. The results show that cross-sectoral synergies are key in capitalizing on the demographic bonus to support inclusive and sustainable economic growth. The research also highlights the importance of developing policies that are adaptive to the needs of the digital era to create a highly competitive workforce. With strong collaboration between the education, health, and economic sectors, the research provides concrete solutions to improve the quality of human capital through technology-integrated education, relevant digital skills training, and well-coordinated cross-sector policies. It was found that cross-sectoral cooperation is key in harnessing the potential of the demographic bonus to support inclusive and sustainable economic growth. In addition, this research emphasizes the need for policies responsive to the development of the digital era to create a highly competitive workforce in the global market.